2001
DOI: 10.1051/0004-6361:20010100
|View full text |Cite
|
Sign up to set email alerts
|

New determination of the solar apex

Abstract: Abstract. Many studies recently have been performed to determine the velocity vector of the Sun, mainly using the latest data on proper motions and parallaxes given by the Hipparcos satellite. We wished to carry out a similar study using totally independent data: the numerous radial velocities (RV ) obtained with the Fehrenbach Objective Prisms (PO). This method allows the determination of the RV s of all the stars contained in the same field. These RV s are relative to each other but are linked to the IAU sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 4 publications
4
45
2
Order By: Relevance
“…This value is in good agreement with the value v rad = +440 km s −1 obtained by Fehrenbach & Duflot (1981).…”
Section: Luminosity and Distance Of The Feh-duf Starsupporting
confidence: 91%
See 1 more Smart Citation
“…This value is in good agreement with the value v rad = +440 km s −1 obtained by Fehrenbach & Duflot (1981).…”
Section: Luminosity and Distance Of The Feh-duf Starsupporting
confidence: 91%
“…The Fehrenbach & Duflot star (=2MASS J05025386-6544207, hereafter the Feh-Duf star according to SIMBAD designation) was discovered in 1981 by Fehrenbach & Duflot (1981) during their measurements of radial velocities of stars in the region of the Large Magellanic Cloud. They found that this star has a very high radial velocity (+440 km s −1 ) and also displays exceedingly strong CH absorption bands in its spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Their radial velocities showed that the star had a radial velocity range of nearly 20 km s −1 , indicating that it is likely to be a spectroscopic binary. Kaye & Fekel (2003) used the velocities of Fehrenbach et al (1987) and Henry & Fekel (2002) to obtain a preliminary orbit with a period of 31.95 days.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a distance modulus of the LMC The systematic separation of stars in the direction of the Magellanic Clouds into member stars and galactic foreground stars has been initiated by Fehrenbach & Duflot (1970). These first lists were supplemented by numerous authors (Ardeberg et al 1972;Fehrenbach & Duflot 1973, 1974Brunet et al 1973Brunet et al , 1975Isserstedt 1975aIsserstedt , 1979Isserstedt , 1982Rousseau et al 1978) with additional stars and photometric measurements. However, there are problems in combining these data:…”
Section: The Bochum Lmc Photometry Data Basementioning
confidence: 99%